Jamaican Field Cricket, Gryllus assimilis (Fabricius) (Insecta: Orthoptera: Gryllidae) - Thomas J. Walker (EDIS)
This species was first described from Jamaica and is widespread in the West Indies. It may have first become established in south Florida as recently as the early 1950's. Its scientific name (Gryllus assimilis or Acheta assimilis) was applied to all New World field crickets until 1957. This document is EENY-069, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 1999. Reviewed: May 2003.